CRM development in hospitality companies for the purpose of increasing the competitiveness in the tourist market - Slobodan Ivanovic; Kresimir Mikinac; Luka Perman (UTMS Journal of Economics, 2011)
CRM as a trend in business and business philosophy consists of a series of complex and diverse business resources such as: modern technological resources, information resources, human resources and all other procedural resources which serve to improve services to end user and customer. Tourism as a service industry which business is based on selling services, has found great benefits and advantages in using CRM. Different kinds of CRM applications and systems have become extremely popular in all sectors. Thus, in the tourism sector, CRM has become one of the most important strategy in attracting and increasing tourist arrivals, in filling the tourist facilities and in satisfying the needs of guests. The main goals of CRM are to attract tourists, to meet a maximum of tourists (a new guarantee of return and achieve the most efficient promotion), increase the number of tourists and achieve customer loyalty. It enables more efficient marketing and sales and it improves the overall tourism industry and services aimed at tourists and their preferences. Implementation of CRM systems is very demanding and requires commitment at all levels of the company. Very big problem is the integration of CRM systems with existing information systems in the enterprise. It is often impossible to implement without the use of qualified personnel and software that has the task of bridging the gulf between the CRM and existing information systems to create an integrated system. It is desirable that the companies have been devoting increased funding for implementation of new technologies and that systems, in a short period of time, can realize a return on investment and greatly improve the business performance of enterprises. CRM gives the expected results only if it is fully integrated strategically and operationally in the business and in the information system of tourist enterprise. The fact is that this process and business philosophy will become important in the future, and it will continuously improve its processes and relationships within the company, all in order to reduce operating costs, creating a detailed segmentation of the market and meet the needs of guests.
Keywords: 330; CRM; tourism; information systems; new technologies.